50. POSTOPERATIVE VISUAL LOSS IN THE PRONE POSITION SPINE SURGERY: A CASE REPORT (Vietnam Journal of Community Medicine, 2025)
Background: Postoperative visual loss in the prone position spine surgery is very rare, but this complication can result in severe consequences. Common causes include ischemic optic neuropathy, central retinal artery occlusion, and cortical blindness. Risk factors include peripheral vascular disease, hypertension, anemia, and diabetes mellitus with end-organ damage.Objective: Identify the causes and prevention of postoperative visual loss in the prone position spine surgery due to acute angle-closure Glaucoma.Materials and methods: A case report, describes a 62-year-old female patient who was scheduled for decompression and spinal fusion surgery at the L4-S1 levels due to lumbar disc herniation and spinal canal stenosis at L4/L5 and L5/S1.Results: After surgery, the patient complained of eye pain, blurred vision, and redness in both eyes, along with generalized edema. Ophthalmologic examination revealed acute angle closure in both eyes, with a provisional diagnosis of angle-closure Glaucoma. The treatment plan included initial medical management, followed by eye surgery once spinal postoperative recovery was stabilized.Conclusion: Postoperative visual loss in the prone position spine surgery is a rare but serious complication, for which the most effective treatment remains prevention.
Keywords: Postoperative visual loss, spine surgery, prone position, angle-closure Glaucoma.